STRATEGI MITIGASI RISIKO DALAM RANTAI PASOK PRODUKSI SAYURAN ORGANIK DARI ASPEK EKONOMI BERBASIS PENDEKATAN HOR: Risk Mitigation Strategy in The Supply Chain of Organic Vegetable Production from Economic Aspects Based on A HOR Approach - Anindita Rahmalia Putri (Universitas Darussalam Gontor, 2022)
Awareness of healthy food consumption has pushed the organic farming supply chain to further increase its productivity. This is not in line with the dynamic conditions of the organic farming supply chain. Dynamic conditions such as climate uncertainty, pest intervention to fluctuating market demand sometimes become obstacles for supply chain actors. In the organic farming supply chain, the production of organic vegetables poses the greatest risk and can disrupt the flow of products to consumers. These obstacles will directly cause losses for farmers. So to minimize these obstacles, a risk mitigation strategy design is needed. This study aims to design appropriate risk mitigation strategies in organic vegetable production. The research located in D.I Yogyakarta took respondent data consisting of farmers, CV owners, employees and experts in the field of organic agriculture. The focus of this research is the design of risk mitigation strategies from the economic aspect using the House of Risk (HOR) method on the production of organic vegetables from the organic farming supply chain. The results show that the source of risk that has the largest aggregate value is an uncertain climate with a value of 1701. And to minimize the potential for these risks, there are 12 mitigation strategies that can be applied. The risk mitigation strategy that has the highest rating with a value of 14850 is the existence of crop management that regulates the planting time between plants.